Dispute Prevention in Culinary Business Transactions: An Introduction to ADR/Arbitration Clauses for MSMEs - Muntazhor, Ahmad Widad; Wibowo, M. Arief Noer; Aurelia, Farah (Unram Journal of Community Service, 2025)
This Community Service Program aimed to introduce the concept of Alternative Dispute Resolution (ADR), particularly arbitration, as a preventive approach in managing business dispute risks within micro, small, and medium-scale culinary enterprises. Culinary-based MSMEs generally rely on trust and informal communication in their commercial transactions, making them vulnerable to conflicts arising from differences in interpretation, delayed payments, price changes, or contract breaches. Through this program, participants were provided with knowledge of the legal position of arbitration as a dispute-resolution forum outside the state court system, the final and binding nature of arbitral awards, and the importance of incorporating simple arbitration clauses into business agreements as a tool for dispute prevention. The activity was implemented using a combination of lecture, discussion, and question-and-answer methods. The results show that participants demonstrated a high level of interest due to limited access to information related to non-litigation dispute resolution mechanisms. Participants also acknowledged that inserting simple arbitration clauses—even in order forms commonly used in day-to-day operations—constitutes a realistic approach. This program has encouraged an increased awareness of the need for more structured contractual practices as part of improving business governance among MSMEs. It is expected that this knowledge could stimulate MSMEs to develop transactional systems that not only rely on trust but are also equipped with adequate preventive instruments, thereby strengthening the stability, security, and competitiveness of their business practices.